2002
DOI: 10.1038/sj.bjp.0704642
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic agonist potencies at three different effector systems linked to the M2 or M3 receptor in longitudinal smooth muscle of guinea‐pig small intestine

Abstract: 1 The abilities of muscarinic agonists (arecoline, bethanechol, carbachol, methacholine, pilocarpine) to inhibit isoprenaline-induced cyclic AMP production in chopped fragments (via M 2 receptors), and to evoke cationic current (I cat ) (via M 2 receptors) or calcium store release (via M3 receptors) in enzyme-dispersed, single voltage-clamped cells from longitudinal smooth muscle of the guinea-pig small intestine were examined. 2 All muscarinic agonists (1 ± 300 mM) examined inhibited isoprenaline (1 mM)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 36 publications
0
36
1
Order By: Relevance
“…This is supported by the observation that M2-receptor antagonists inhibited carbachol-evoked I cat in a competitive manner, while M3-receptor antagonists severely depressed its maximum response, under conditions where [Ca 2+ ] i was buffered to a certain level (5). Under the same conditions, significant correlations of agonist potencies between for I cat activation and M3-receptor stimulation have also been found (16). However, the mechanisms underlying the synergistic activation of I cat by M2 and M3 receptors remain to be elucidated.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…This is supported by the observation that M2-receptor antagonists inhibited carbachol-evoked I cat in a competitive manner, while M3-receptor antagonists severely depressed its maximum response, under conditions where [Ca 2+ ] i was buffered to a certain level (5). Under the same conditions, significant correlations of agonist potencies between for I cat activation and M3-receptor stimulation have also been found (16). However, the mechanisms underlying the synergistic activation of I cat by M2 and M3 receptors remain to be elucidated.…”
Section: Introductionmentioning
confidence: 59%
“…Upon its application, I K-Ca lasting 3 -10 s was elicited, as described (6,16) (Fig. 1A), whose amplitude amounted to 3.90 ± 0.63 nA on the average (n = 6).…”
Section: Effectiveness Of U73122 and Ga Q /Ga 11 -Antibody In Inhibitmentioning
confidence: 70%
See 1 more Smart Citation
“…1). A similar outward I K-Ca (mean amplitude: 2866 ± 414 pA, n = 5) was also evoked by a potent Ca 2+ -store releaser, caffeine (10 mM), which was capable of depleting stored Ca 2+ in guinea-pig ileal myocytes (20). After the initial outward I K-Ca evoked by caffeine, brief, spontaneous outward I K-Ca no longer occurred, indicating depletion of internal Ca 2+ stores.…”
Section: +mentioning
confidence: 69%
“…3B, 3C, 5A, and 5B, AF-DX116 (30 nM) and 4-DAMP (10 nM) each exerted more than 50% inhibition of both carbachol-induced IMF contraction and [Ca 2+ ] i elevation. A recent study reported that activation of muscarinic M 3 receptor can potentiate the muscarinic M 2 receptor signal by opening of cationic channels in smooth muscle cells (30). Another report suggested that muscarinic M 2 receptor activation strengthens muscarinic M 3 -mediated contraction by decreasing K + efflux (15).…”
Section: Discussionmentioning
confidence: 99%